2019
DOI: 10.1002/hed.25804
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of fine‐needle aspiration cytology of parotid neoplasms based on the Milan system—Experience from a tertiary center in Asia

Abstract: Background The recently described Milan system provides a unified way of categorizing salivary gland fine‐needle aspiration (FNA) cytology. We aim to use this system to stratify risk of malignancy in parotid FNAs. Methods In this retrospective case series, 376 FNAs were preoperatively performed for 573 parotidectomies over 14 years. Results Risk of malignancy on FNA is as follows: nondiagnostic 14.5%, non‐neoplastic 26.7%, atypia of undetermined significance 29.3%, benign neoplasm 2.7%, neoplasm of uncertain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 24 publications
5
27
1
Order By: Relevance
“…Indeed, PA and Warthin's tumours were the most frequent diagnoses (respectively 27.1% and 16.8% of total cases). This is consistent with the frequency reported in the literature [9,10,14,15]. These diagnoses are indeed straightforward for representative samples.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, PA and Warthin's tumours were the most frequent diagnoses (respectively 27.1% and 16.8% of total cases). This is consistent with the frequency reported in the literature [9,10,14,15]. These diagnoses are indeed straightforward for representative samples.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous fibroblasts were present in this lesion and these cells have been confused with atypical cells on cytological smears. The RON and ROM for SUMP category, oncocytic SUMP subtype and unspecified SUMP subtype are consistent with the MSRSGC and previous studies [3,6,14,15]. The SM category was also seldom used since it represented only 4.9% of our cases.…”
Section: Discussionsupporting
confidence: 90%
“…The RON and ROM in our series was 50% in ND category, which is higher than quoted by Milan group that is 25%, but still within the range of 0%‐67% . The ROM in the study by Choy et al was 14.5% which was much lower than our study . The high RON and ROM in our study were due to the low number of patients with surgical follow up in this category.…”
Section: Discussioncontrasting
confidence: 80%
“…The RON and ROM were 93% and 14% in our series. The ROM in our series was lesser than reported by Wei et al—37.5% ± 24.7%, Viswanathan et al—34.2% and Song et al—46.4% and even lesser than ROM quoted by the Milan group of 35% . Chowsilpa et al had reported a RON of 95.4% which was similar to ours, and a ROM of 33.8% which was higher than our study .…”
Section: Discussionsupporting
confidence: 64%
“…In addition, the uniform terminology allows cross communication between pathologists and institutions. Since the print publication of the MSRSGC in 2018, many institutions across the world retrospectively applied this tired diagnostic scheme to their institutional cohort of cases or those collected from multiple institutions and reported their findings with and without surgical follow‐up 6‐43 …”
Section: Introductionmentioning
confidence: 99%